Resolusi Konflik Berbasis Digital dalam Pendidikan di Madura - Devi Maulidya Putri; Moh. Rayhan Arraofi; Farikha Hasanah; Maimun Maimun (Journal of Communication in Tourism, Culture and Education, 2025)
This article discusses the role of digital technology, particularly social media, in conflict resolution in the educational context in Madura. Digital technology offers a fast and efficient solution for addressing tensions between students, teachers, and parents through communication platforms such as WhatsApp and Facebook. However, its implementation in Madura faces significant challenges, such as the digital divide, limited infrastructure, and low digital literacy among the community. The local culture, which tends to prioritize conventional methods of conflict resolution, also hinders the acceptance of digital technology. Case studies show that although social media can enhance communication and accelerate problem-solving, a lack of awareness and digital skills can affect its effectiveness. Therefore, there is a need to improve digital literacy and understand local culture to ensure digital technology is effectively integrated into conflict resolution in Madura’s educational setting